ANALISIS WAKTU PEMASAKAN DALAM PROSES PEMBUATAN PERMEN MADU Trigona biroi DAN Apis dorsata - Maria Maria; Hadija Azis Karim; Muh Nuh (Universitas Andi Djemma Palopo, 2021)
Honey candy is an innovation in the field of utilizing honey for hygienic consumption, and honey has a high value if it is processed into a candy innovation. This study aims to determine the process of making real honey candy and the ratio of initial and post-cooking weight of two types of honey, namely Trigona biroi honey and Apis dorsata. The data used in this study are secondary and primary data. Data collection took place for 1 month, from September to October 2020 in Waetuo VillageWest Malangke North Luwu. Data were collected from experimental results. This study uses quantitative descriptive analysis presented in the form of tables and paragraph descriptions that provide an overview of the object under study through sample and population data. The results of this study indicate that the weight ratio of Trigona biroi and Apis dorsata honey where the cooking time and honey quality will affect the honey weight. So that in Trigona biroi honey, the water content is higher than that of Apis dorsata. The cooking time for Trigona biroi is 5 minutes to 15 minutes, the final weight is 11 grams, 8 grams and 5 grams. while the final weight of Apis dorsata is 18 grams, 16 grams and 14 grams.